Risk factors for, and the effect of MRSA colonization on the clinical outcomes of severely burnt patients. Issue 6 (September 2015) - Issler-Fisher, Andrea C.; McKew, Genevieve; Fisher, Oliver M.; Harish, Varun; Gottlieb, Thomas; Maitz, Peter K.M.
Highlights Extensive analysis of risk factors for and the outcome of MRSA positivity in over 350 burn patients. We show a significant negative impact of MRSA positivity on burn patients' outcome. Our findings stress the need for further efforts toward MRSA infection control and screening procedures.